PENGGUNAAN BUSINESS MODEL CANVAS (BMC) SEBAGAI METODE PERENCANAAN BISNIS GUNA MENGURANGI PENGANGGURAN TERDIDIK - Andi Nuril Ainul Yaqin Bunyamin; Muh. Rajan Piara (Bussman Journal : Indonesian Journal of Business and Management, 2023)
The problem of unemployment is currently still a big problem in almost all countries, especially in developing countries. One of the developing countries is Indonesia. Unemployment today can result from the increasing difficulty of finding a job, especially in big cities. One of the characteristics of unemployment in Indonesia is unemployment that has a fairly high education or commonly referred to as educated unemployment. One of the plans that can be used is to use the Business Model Canvas (BMC).      The research method used in this study is literature review. Literature review or literature review research is the process by which research is sought, explored, read, and evaluated. The results obtained are that the convenience provided using BMC tools with a simple picture poured on the canvas provides benefits for prospective business actors in determining the focus that will be a strategy in achieving goals